Al-Kindi: Filsuf Muslim Pertama dan Relevansinya dalam Pendidikan Islam Kontemporer - Amalia, Milda; Sya’roji, Sya’roji (Intelektualita: Journal of Education Sciences and Teacher Training, 2024)
Al-Kindi is known as the first Muslim philosopher who played an important role in harmonizing Greek philosophy with Islamic teachings. His rational and integrative thinking made a significant contribution to the development of Islamic science and education. This article analyzes the influence of Al-Kindi's thought in contemporary Islamic education by reviewing the relevance of his rational and epistemological approach in the modern context. Through literature study methods and content analysis, this study finds that Al-Kindi's thinking can be the foundation for holistic Islamic education by combining science and religious values in a balanced manner. The results of the study show that the integration of science and religion offered by Al-Kindi is able to encourage critical, analytical, and creative thinking in Islamic education. In addition, Al-Kindi's rational approach has proven relevant in developing an Islamic education curriculum that is adaptive to the development of science and technology. This article concludes that Al-Kindi's thought made a significant contribution in creating Islamic education that is relevant to the needs of the times and is able to produce a generation that is intellectually intelligent and has noble character.